Kinder - ein Quell der Freude?! - Stephan Humpert (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
– It is well known, that the presences of children lower parental happiness. That is based on psychological and economical reasons. The effect holds on for micro data of the GSOEP. The number of children affects an inverse u-shaped curve on happiness. Even an enlargement of the dataset with macroeconomic variables offers the same results. The effect disappears only after generating terms of interaction for catching some effects of macroeconomic uncertainty. Children turn to be positive. This result could be interpreted as consumption utility of children. Considering these factors, children might be a source of joy.
Keywords: I31; J13; 330; Happiness; children